KETERAMPILAN TEKNIS DAN SOFT SKILLS LULUSAN D3 TEKNIK SIPIL YANG DIBUTUHKAN PERUSAHAAN KONSULTAN DI KOTA PADANG - Ruslaini .; Drs. Juniman Silalahi, M.Pd (CIVED, 2019)
Absrack – This research was motivated by the workforce of Civil Engineering D3 graduates who still lacked the technical skills and soft skills that worked in consulting companies in the City of Padang. This research was conducted to reveal the technical skills and soft skills of D3 Civil Engineering graduates needed at a consulting company in the City of Padang. This type of research is quantitative with a descriptive approach. The population in this study is 41 consulting companies in the Inkindo and Perkindo associations. The sample is taken as a whole (Total Sampling). Primary data is obtained through the provision of questionnaires (questionnaires) to the leadership or consultant manager site. While secondary data is in the form of data from consulting companies in the Perkindo and Inkindo Associations that have been registered in 2017 in the City of Padang. Data analysis techniques used are: 1) Data Verification, 2) Descriptive Analysis. The results showed that much-needed technical skills from D3 Civil Engineering graduates at a consulting company in Kota Padang were: Drawing with Software (Auto CAD), Calculating RAB, Experts, Performing Measurements (Quantity Surveryor), Construction Management and Working Drawing Reading . While the soft skills that are very much needed are: Work in Teams, Motivation, Ethics/integrity, Mandiri, Time Management, Oral Communication, Critical Thinking and Loyalty. Keywords: Technical Skills, Soft Skills, Manpower D3 Civil Engineering Graduates.